Sodi Alvarez, Enrique. Istmo de Tehuantepec - José Salgado y Salgado (Revista Mexicana de Ciencias Políticas y Sociales)
Sodi Alvarez, Enrique. Istmo de Tehuantepec. México, Puertos Libres Mexicanos, 1967, 204 pp.